The influence of pig breed and pedigree on the quality characteristics of meat - Pankova E.K.; Polkovnikova V.I. (BIO Web of Conferences)
One of the promising tasks in pig breeding is considered to be the targeted cultivation of hybrid pigs, from which high meat productivity can be obtained. The research was carried out at the pig farm of Golden Calf LLC in the Tchaikovsky district of the Perm Territory. The meat qualities of purebred and crossbred animals, biochemical parameters of blood serum of young animals, morphological, chemical, and organoleptic composition of pig carcasses were studied. Pork obtained from two-breed animals had good morphological, chemical and organoleptic properties. Nevertheless, slightly worse technological pH values were observed in the meat of young animals obtained by crossing the large white and Duroc breeds, which could indicate a tendency to PSE defect. Perhaps this result was due to overexposure of fattening animals, since the Duroc breed is considered more precocious among other breeds. In general, according to the biochemical analysis of blood serum, it turned out that all the studied animals were healthy.